The Effects of Management Control Systems on Service Quality Performance in Malaysian Local Authorities: Management Perspective - Ilias, Norazlina; Abdulatiff, Nik Kamaruzaman; Wan Zakaria, Wan Zuriati; Wahab, Norlidawahi (International Review of Management and Marketing, 2016)
Management control systems provide different valuable information which is relevant to the needs of managers at different levels in the organization. However, there is a lack of empirical evidence about how the management control systems affect the service quality performance of local authority especially in Malaysia. Through the semi-structured interviews in the preliminary survey in four local authorities in East Coast Region of Malaysia, the aim of this study is to provide evidence of the existence of management control systems practices in Malaysian local authorities and to examine the effects of the management control systems on service quality performance. The results revealed that local authorities with high concerning of internal control secure better results in service quality performance as compared to local authorities with less concerning of internal control.